SOSIALISASI PEMBERDAYAAN MASYARAKAT DESA DALAM MENURUNKAN ANGKA KEMISKINAN DAN STUNTING - Devit Bagus Indranika; Suryoto; Anggara Setya Saputra; Iin Piani; Eka Kusumaningtias; Lita Ningrum Afriani (Department of Public Administration, University Wijaykusuma Purwokerto, 2024)
Poverty reduction programs are part of the overall target of development programs. Various priority issues mandated include poverty alleviation and stunting reduction. It is the duty of stakeholders in villages and regions to carry out innovations with the aim of the success of the national program. The purpose of writing this service article is to provide a reference to stakeholders to produce a community empowerment program to reduce poverty and stunting rates in Banyumas Regency. The method was carried out using focus group discussion techniques. The results show that community empowerment in the context of poverty alleviation and handling stunting in Banyumas Regency is important. The importance of implementing poverty alleviation in villages is very large. Village Funds are used for basic infrastructure development and village community empowerment, which is an important step in reducing poverty in rural areas. Poverty alleviation strategies through community empowerment programs are also considered important, because they can increase the income and quality of life of village communities. In addition, efforts to eradicate village poverty are considered a priority to create a just and prosperous society. Studies also show that the effectiveness of Village Funds contributes to poverty alleviation and improving development performance in rural areas. Therefore, implementing poverty alleviation in villages has a significant impact in improving the welfare of rural communities. Regularly evaluating poverty alleviation programs is important to ensure their effectiveness and efficiency.